2017
DOI: 10.1038/s41437-017-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Geographical isolation and environmental heterogeneity contribute to the spatial genetic patterns of Quercus kerrii (Fagaceae)

Abstract: Southwest China is one of the major global biodiversity hotspots. The Tanaka line, extending within southwestern China from its northwest to its southeast, is an important biogeographical boundary between the Sino-Japanese and Sino-Himalayan floristic regions. Understanding the evolutionary history of the regional keystone species would assist with both reconstructing historical vegetation dynamics and ongoing biodiversity management. In this research, we combined phylogeographic methodologies and species dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 62 publications
(81 reference statements)
1
41
0
Order By: Relevance
“…Coordinates of these specimens were then used to extract 19 BIOCLIM variables from WorldClim 1.4: Current conditions (~ 1960–1990) [128] using the raster [129] and dismo packages [129] in R. Geographic records of sections Cyclobalanopsis , Ilex and Quercus were obtained from our field collection database, Chinese Virtual Herbarium (http://www.cvh.ac.cn), Global Biodiversity Information Facility (https://www.gbif.org) and National Herbarium of the Netherlands (http://herbarium.naturalis.nl/nhn/explore). Additional geographic occurrence data were added from previous studies for section Cyclobalanopsis [3638, 130], section Ilex [39, 43, 47, 131], and section Quercu s [29, 50, 130, 132–134]. The sampling records of sections Ilex and Quercus were uneven, which would have affect climate analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coordinates of these specimens were then used to extract 19 BIOCLIM variables from WorldClim 1.4: Current conditions (~ 1960–1990) [128] using the raster [129] and dismo packages [129] in R. Geographic records of sections Cyclobalanopsis , Ilex and Quercus were obtained from our field collection database, Chinese Virtual Herbarium (http://www.cvh.ac.cn), Global Biodiversity Information Facility (https://www.gbif.org) and National Herbarium of the Netherlands (http://herbarium.naturalis.nl/nhn/explore). Additional geographic occurrence data were added from previous studies for section Cyclobalanopsis [3638, 130], section Ilex [39, 43, 47, 131], and section Quercu s [29, 50, 130, 132–134]. The sampling records of sections Ilex and Quercus were uneven, which would have affect climate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Oak plastome haplotypes have been widely sampled, particularly in three major clades: sections Cyclobalanopsis and Ilex , which have an East and Southeast Asian and Eurasian (sub) tropical distribution, respectively; and section Quercus , which is widely distributed in the Northern Hemisphere [27]. Recent phylogeographic studies of the species of section Cyclobalanopsis [3638] indicated that landscape, climate and local adaptation shape regional genetic diversity patterns. Similarly in section Ilex , geomorphological and climate changes from the Neogene onward have been demonstrated to have shaped the genetic structure [3947].…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuating environmental conditions, including variation in the local or regional climate, can induce severe stress that can considerably alter the genetic variation of a species through divergent selection processes [15], and may lead to increased genetic differentiation between populations on a spatial scale [16]. Environmental variability (or heterogeneity) has long been recognized as an important driver of genetic variation and differentiation [17, 18], and several studies have also shown statistical associations between neutral genetic variation and environmental heterogeneity [1922]. The latter correlations may be interpreted as evidence of diversifying selection acting over whole genomes, including on putatively neutral loci, and allows us to infer the long-term effects of environmental conditions on genetic variation [19, 23].…”
Section: Introductionmentioning
confidence: 99%
“…Forests play crucial roles in both the regional ecology and economy, including maintaining species diversity, regulating climate, conserving water and soil, and providing timber and food [1,2]. A great deal of research is still required to better understand and untangle the biotic and abiotic factors that drive speciation, genetic differentiation, and the distribution dynamics of trees [3][4][5][6]. The demographic history and distribution dynamics of trees can be reconstructed based on a species genetic diversity, paleontology data, and a species distribution model, or the combination of these data [7,8].…”
Section: Introductionmentioning
confidence: 99%